THE EFFECT OF PROBLEM-BASED LEARNING STRATEGIES AND SCORING MODELS TOWARDS MATHEMATICS ACHIEVEMENT BY CONTROLLING STUDENTS’ INTELLIGENCE - Khasanah (lppm Universitas Negeri Jakarta, 2015)
The study was aimed to find out the influence of problem-based learning strategies and scoring models towards mathematics achievement by controlling studentsâ€™ intelligence. The research method used in this study is an experimental method. Meanwhile, the design used in this research was the factorial design of 2Ã-2 and research hypotheses were tested by using covariant of analysis (ANCOVA). The participants of this study were 100 students from tenth grade in SMAN 55 and SMAN 60 Jakarta. The study concluded that after controlling studentsâ€™ intelligence: (1) mathematics achievements of the students who were given the problem posing strategy was higher than that of those who were given the problem solving strategy, (2) mathematics achievements of the students who were given the correct score model was higher than that of those who were given the punishment score model, (3) there was an interaction effect between problem-based learning strategies and scoring models towards mathematics achievement, (4) especially for groups of students who were given Problem Posing Strategy, mathematics achievement of the students who were given the correct score model was higher than that of those who were given the punishment score model, (5) especially for groups of students who were given problem solving strategy, mathematics achievement of the students who were given the correct score model was lower than that of those who were given the punishment score model, (6) especially for groups of students who were given the correct score model, mathematics achievement of the students who were given problem posing strategy was higher than that of those who were given the problem solving strategy, and (7) especially for groups of students who were given the punishment score model, mathematics achievement of the students who were given the problem posing strategy is lower than that of those who given the problem solving strategy. Thus, it can be recommended to the teachers to use the problem posing strategy and the correct score model.